SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PEMBERIAN KREDIT MOBIL MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DI CV. ANGKASA MOBIL FINANCE - Bima Gilang Pamukti; Naniek Widyastuti; Erfanti Fatkhiyah (Jurnal SCRIPT, 2016)
The economic system in Indonesia is conducting economic transaction whether pay by cash or by credit. Most of Indonesian citizen understand both methods, especially the credit model which proved by high interest of Indonesian society to this model which this model is used in all economic sector, including car. It would be more beneficial if computer technology is able to support credit analysis in making a decision that is capable of assessing the appropriateness of car credit. This Decision Support System is able to support the problem solving efficiently and effectively. This application is designed by using diagram context and data flow diagram, whereas it is programmed by using PHP programming language, MySQL database and Analytical Hierarchy Process (AHP). This research is concerned on knowledge and feasibility problems of providing car credit; in this case it will be used by the company of CV. Angkasa Mobil Finance into a computer application which is capable of performing calculations in a short time. So this application could support the credit analysis in providing car credit to right prospective creditor in the short future.